21‐1: Invited Paper: Polarized Emission Thin‐Film Light‐Emitting Diodes. Issue 1 (28th June 2022) - Dong, Qi; Zhu, Liping; Yin, Shichen; So, Franky
Abstract : Organic light emitting diodes (OLEDs) with controlled light emission have many photonic applications. In this paper, using OLEDs for demonstrations and different photonic structures, we demonstrated highly polarized light emission from an OLED. The highly selective diffraction of only the TE waveguide mode is possible by selectively diffracting the TE waveguide mode while suppressing other optical modes. Similar devices are made with perovskites to achieve a current efficiency of 56 cd/A.